Skin ulceration as a complication from unexpected extravasation injury: A case report - Hock Chin Chong; Kean Khang Fong; FirdausHayati (Elsevier Ltd, 2021)
Extravasation injury (EVI) is common, yet it is always underestimated and underreported. Severity varies ranging from thrombophlebitis up to disability. Unrecognised EVI is a potential medicolegal case in medicine. We experience a 47-year-old lady who developed an unrecognised EVI after being admitted for sepsis. The EVI turned out to be a huge and sloughy skin ulcer. A series of wound debridement with vacuum dressing were conducted until the wound was able to be closed. The EVI can be categorised according to Amjad EVI grading and Loth and Eversmann’s EVI classification. Adult EVI tends to be overlooked, especially during critical care because patients cannot complain upon sedation and ventilation. In order to prevent EVI, firstly prevention is better than cure. Secondly, if EVI is recognised early, infusion should be stopped immediately. Thirdly, analgesia is mandatory. Finally, the plastic team needs to be engaged if it is deemed required. Prevention and early intervention before the occurrence of progressive tissue damage is the key to treatment. Early radical wound debridement and immediate or delayed wound coverage with skin graft or skin flap are indicated in full thickness skin necrosis, persistent pain, and chronic ulcer.